On Six Solutions for m-Point Differential Equations System with Two Coupled Parallel Sub-Super Solutions - Jian Liu; Hua Su; Shuli Wang (Journal of Applied Mathematics)
Under the assumption of two coupled parallel subsuper solutions, the existence of at least six solutions for a kind of second-order m-point differential equations system is obtained using the fixed point index theory. As an application, an example to demonstrate our result is given.